PENGARUH STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN - Nini, Nini (Journal of Innovation Research and Knowledge, 2022)
The purpose of this study is to examine the effect of capital structure, company growth and company size on company performance in all manufacturing companies listed on the Indonesia Stock Exchange for five years from the 2015-2019 period. The capital structure variable is measured by market short-term leverage (MSLEV), Short-Term Debt to Asset (STDTA). The firm size variable is measured by (SIZE) and the firm's performance variable is measured by the Return on Equity (ROE) ratio. While the population in this study are all manufacturing companies listed on the Indonesia Stock Exchange. The final sample was obtained as many as 420 companies for five years using purposive sampling method. Then for the type of data in this study, researchers used secondary data obtained from IDX using multiple regression analysis method. The results of this study indicate that the capital structure based on market value measurement (MLLEV) in linear regression has a negative and significant effect. Capital structure based on book value measurement (LTDTA) has a positive and significant effect. Firm size (SIZE) has a significant positive effect on firm performance.